2021
DOI: 10.1177/1745506521998204
|View full text |Cite
|
Sign up to set email alerts
|

The act of telling: South African women’s narratives of HIV status disclosure to intimate partners in the HPTN 071 (PopART) HIV prevention trial

Abstract: Background: Public health programming often frames HIV status disclosure as a means to negotiate condom- and abstinence-based prevention or to involve intimate partners in HIV care to garner treatment adherence support. HIV treatment can be used to ensure viral suppression and prevent onward transmission, which provides strong evidence to encourage disclosure. The ideological shift towards HIV treatment as prevention is expected to facilitate disclosure. Purpose: There is a lack of research on how the scale-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Deliberate non-disclosure of HIV status may be a function of personal interests or priorities to avoid loss of trust and ensure self-preservation while simultaneously (re)constructing self-identity and reaffirm or redefine existing social interactions with the spouse/intimate partner (56). This probably may also have been the case in our study where 1.8% of women had an undisclosed HIV status, up to 7,259 days after being diagnosed of HIV.…”
Section: Non-disclosure Of Hiv Status and Stigmamentioning
confidence: 75%
“…Deliberate non-disclosure of HIV status may be a function of personal interests or priorities to avoid loss of trust and ensure self-preservation while simultaneously (re)constructing self-identity and reaffirm or redefine existing social interactions with the spouse/intimate partner (56). This probably may also have been the case in our study where 1.8% of women had an undisclosed HIV status, up to 7,259 days after being diagnosed of HIV.…”
Section: Non-disclosure Of Hiv Status and Stigmamentioning
confidence: 75%
“…There are fewer reports in the literature relating to facilitators of HIV status sharing. Viljoen et al [ 36 ] reported that trust and intimacy can motivate sharing. HIV status sharing in young people with PAH has been associated with higher levels of HIV disclosure self-efficacy, being older, paternal orphanhood, contributing to family income, regular visits to the HIV clinic, and greater social support through peers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adapting strategies used to address HIV stigma, including the prioritization of rights-based approaches and empowerment, can help to change narratives surrounding TB. This includes eliminating criminalizing and discriminatory terms such as suspect or defaulter that drive stigma ( 14 ), and considering personal rather than only public health motivation to facilitate disclosure conversations ( 39 ). Given stigma’s impact on TB care outcomes as well as longer-term impacts on people’s well-being, we recommend that TB-related stigma should be evaluated and measured as a primary indicator of quality-of-life rather than merely as a programmatic or medicalized indicator of the TB cascade ( 8 ).…”
Section: Discussionmentioning
confidence: 99%